Multimodal Semiotic Analysis From Poster Captain America Series - Sabrina Putri Octaviani (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
The purpose of this study is to examine the multimodal aspects of the Captain America series posters, focusing on how the combination of images, text, and color constructs meaning and shapes audience perception. This study employs a semiotic analysis approach to explore the visual symbolism present in elements such as characters, backgrounds, and typography. By analyzing these components, the research seeks to understand how visual and textual elements interact to communicate particular messages to viewers. The findings indicate that the posters do not merely present heroic imagery but also convey broader social and political themes, including patriotism, national identity, and moral conflict. Visual elements such as costume design, color schemes, and character positioning reinforce symbolic meanings associated with heroism, power, and ideological struggle. In addition, the textual elements and layout contribute to strengthening the narrative and guiding audience interpretation. Drawing on semiotic theories proposed by Roland Barthes and Gunther Kress, this study highlights how multimodal resources work together to produce layered meanings within popular media. Overall, the study demonstrates that multimodality plays a significant role in constructing identities, narratives, and ideological messages in film posters. These findings are expected to enhance understanding of the relationship between visual and textual communication in contemporary popular culture.